2008
DOI: 10.1128/ec.00029-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Thermotolerance by Stress-Induced Transcription Factors in Saccharomyces cerevisiae

Abstract: The heat shock transcription factor Hsf1 and the general stress transcription factors Msn2 and Msn4 (Msn2/4) are major regulators of the heat shock response in Saccharomyces cerevisiae. Here, we show that transcriptional activation of their target genes, including HSP104, an antistress chaperone gene, is obligatory for thermotolerance. Although Hsf1 activity might be necessary before the exposure of cells to high temperature, severe heat shock induced the binding of hyperphosphorylated Hsf1 to its target promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 55 publications
(96 reference statements)
2
40
0
Order By: Relevance
“…Complementation of rtr1⌬ restored GAL1 induction, verifying that loss of transcriptional activity was due to loss of Rtr1 function (data not shown). Interestingly, RNAPII-but not RNAPIII-dependent gene expression appeared to be inhibited at high temperatures, as is consistent with a previous report (67). FIG.…”
Section: Figsupporting
confidence: 92%
“…Complementation of rtr1⌬ restored GAL1 induction, verifying that loss of transcriptional activity was due to loss of Rtr1 function (data not shown). Interestingly, RNAPII-but not RNAPIII-dependent gene expression appeared to be inhibited at high temperatures, as is consistent with a previous report (67). FIG.…”
Section: Figsupporting
confidence: 92%
“…Network analysis of these regulators showed that many regulators are highly connected and interact with each other genetically and biochemically ( Fig. 8) (5,18,44,59,72,80,81,88,91,95,98,106,120,123,128). Many of the regulators are components of global regulatory complexes.…”
Section: Suppression Of Hypoxia Responsiveness Of a Network Of Regulamentioning
confidence: 99%
“…As expected, most of the analyses have shown that heat shock proteins are very important for the thermotolerance, but in addition, several proteins involved in oxidative stress response, signal transduction, transcription, translation, and carbohydrate or nitrogen metabolism were observed (1,19,40). In S. cerevisiae, the heat shock response is mostly controlled by Hsf1, Msn2/Msn4, and Hac1, and targets for these transcription factors have already been identified (22,27,(63)(64)(65)(66). Upon heat shock, the A. fumigatus Hsf1 homologue has increased transcription (1,22).…”
Section: Discussionmentioning
confidence: 59%
“…In the wild-type strain, sebA transcription did not increase in the presence of H 2 O 2 (2 mM) or paraquat (10 mM) for 15 and 30 min or when the strain was exposed to increasing concentrations of KCl and sorbitol (data not shown). The transcriptional response of several A. fumigatus genes involved in the oxidative stress response (http://www.aspgd.org), including Afyap1 and Afatf1 (Afu6g09930 and Afu3g11330), which encode TFs required for resistance to oxidative stress (26,34,65), Afccp1 (Afu4g09110), which encodes a cytochrome c peroxidase (1, 34, 57), Afcat1 (Afu3g02270), which encodes a catalase (57), Afcat2 (Afu8g01670), which encodes a bifunctional catalase-peroxidase (34), afsod1 (Afu5g09240), which encodes a Cu/Zn superoxide dismutase (30,32,34,42,62), and Afusod2 (Afu4g11580), which encodes a manganese-superoxide dismutase (32,57), was assessed via real-time RT-PCR.…”
Section: Resultsmentioning
confidence: 99%